2018
DOI: 10.3390/land7010025
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Modeling of Soil Erosion Risk and Its Implication for Conservation Planning: the Case of the Gobele Watershed, East Hararghe Zone, Ethiopia

Abstract: Abstract:Soil erosion by water has accelerated over recent decades due to non-sustainable land use practices resulting in substantial land degradation processes. Spatially explicit information on soil erosion is critical for the development and implementation of appropriate Soil and Water Conservation (SWC) measures.The objectives of this study were to estimate the magnitude of soil loss rate, assess the change of erosion risk, and elucidate their implication for SWC planning in the Gobele Watershed, East Hara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
83
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(96 citation statements)
references
References 76 publications
11
83
2
Order By: Relevance
“…The LS factor is important because it shows the effect of topography and terrain on the erosion event. Generally, higher slope length and slope steepness will result in higher soil erosion rate (Woldemariam et al 2018). LS factor in Pansoon sub-basin is dominated by low LS factor (74% of below than 5) which means that it has less contribution to the erosion risk.…”
Section: Discussionmentioning
confidence: 99%
“…The LS factor is important because it shows the effect of topography and terrain on the erosion event. Generally, higher slope length and slope steepness will result in higher soil erosion rate (Woldemariam et al 2018). LS factor in Pansoon sub-basin is dominated by low LS factor (74% of below than 5) which means that it has less contribution to the erosion risk.…”
Section: Discussionmentioning
confidence: 99%
“…Soil erosion can also cause severe environmental problems, including soil and water degradation, a decrease in land productivity, and eutrophication and sedimentation of water bodies [3][4][5][6][7][8][9][10][11]. Numerous studies have reported that the magnitude of soil erosion rates has been accelerating worldwide due to land use and land cover change (LULCC) and inappropriate land use and management practices resulting in widespread land degradation process [2][3][4][5][12][13][14][15][16][17][18]. The global annual average potential soil loss due to water-caused erosion was estimated at 35 billion tons in 2001 [4].…”
Section: Introductionmentioning
confidence: 99%
“…In connection to this, the Food and Agriculture Organization (FAO) of the United Nations and Intergovernmental Technical Panel on Soils [14] stated that "if action is not taken to reduce erosion, total crop yield losses projected by the year 2050 would be equivalent to removing 1.5 million km 2 of land from crop production-or roughly all the arable land in India". In the developing countries where the overall economy and the livelihood of a majority of the population depend on the productivity of their land, the displacement of the most productive topsoil layer by erosion and a poor conservation practices have resulted in the reductions in agricultural production and land productivity potential and contributing to food insecurity [18,19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations